Evaluación de habilidades sociales en adolescentes en un contexto escolar (2023)
Currently, students require an elaborate repertoire of social skills to overcome any difficulty and emit more adaptive behaviors in social interaction. This work seeks to determine the state of social skills in adolescents from the Liceo Campestre Fray Arturo Ayala in Paipa-Boyacá. For this, the diagnosis was made by applying the EEHSA instrument (Social Skills Assessment Scale for Adolescents). It was found that both men and women have high initial basic skills, however, in skills to deal with stress and planning skills and decision making their performance was low. This suggests that students have abilities to follow instructions, help others, thank or feel motivated for various activities. However, they perceive themselves as having difficulties to control themselves, face mockery, avoid fights and problems.